Typifications of three names in Elaeocarpus (Elaeocarpaceae) - Gole, Charuta N.; Nimbalkar, Varsha V.; Sardesai, Milind M. (Phytotaxa, 2019)
Elaeocarpus L. is the largest genus of the family Elaeocarpaceae represented by about 350 species worldwide (Coode 2004: 142). The arboreal Old World genus is distributed in subtropical Asia and Pacific Islands to Australia and Madagascar except the African continent (Coode 2004: 137, 138).